FORMULATION AND TESTING OF ANTICONVULSANT ACTIVITY OF TITANUS LEAVES (Leea aequanta L.) ETHANOLIC EXTRACT CAPSULES ON GUINEA PIG (Cavia cobaya) TRACHEA SMOOTH MUSCLE IN VITRO - Dian Ika Perbina Meliala; Sofia Rahmi; Delisma Simorangkir Simorangkir; Beriman Putra Harefa (JBIO: jurnal biosains (the journal of biosciences), 2022)
The main obstacle to consuming traditional medicine is the compounding process which is considered troublesome so that it often causes discomfort to consume it. For the purpose of efficiency, easy and practical in use, need to be made in dosage forms such as capsules. Capsules are solid preparations consisting of a drug in a soluble hard or soft shell. Titanus leaf (Leea aequata L.) is a medicinal plant that is used by the people of the Tanah Karo area, North Sumatra Province as an antitetanus drug. Tetanus is an acute and often fatal disease caused by an exotoxin produced by the bacterium Clostridium tetani. Tetanus often begins with a mild spasm of the jaw muscles which is often referred to as trismus. Sometimes the spasm affects the muscles that help with breathing, which can cause breathing problems. The aim of this study was to formulate EEDT capsules and to test its anticonvulsant activity on the smooth muscle of the guinea pig trachea in vitro. The relaxation effect was tested after the guinea pig's trachea was contracted with acetylcholine (EC80 = 1,0454 x 10-3 M), then the cumulative concentration of EEDT capsules was 0.5-4 mg/mL and atropine sulfate concentration of 6.95 x 10-6 - 2.08 x 10-2 mg/mL. The results of the relaxation effect test showed that EEDT granules could reduce acetylcholine-induced guinea pig trachea smooth muscle contraction. EEDT granules at a concentration of 3.5 mg/mL (102,8817 ± 0,1316) had the same ability as atropine sulfate 6.95 x 10-3 mg/mL (102,7748 ± 0,3231) in reducing guinea pig trachea smooth muscle contraction induced by acetylcholine 1,0454 x 10-3 M (p>0.005). EEDT capsules with a concentration of 3.5 mg and 4 mg had the same effectiveness, that is 102,8817 ± 0,1316. From this study, it can be concluded that the EEDT capsule preparation has a relaxing effect on the smooth muscle of the isolated guinea pig trachea with an ability that is not much different from atropine sulfate.